Identitas Kultural dan Gerakan Politik Kerapatan Adat Kurai dalam Representasi Politik Lokal - IRAWATI, IRAWATI (Jurnal Studi Pemerintahan, 2012)
The strength of ethnic identity became public phenomena later gained momentum in West Sumaterawhen Nagari introducied be formal goverment. The Bukittinggi City Indigenous groups powerincorporated in Kerapatan Adat Kurai (KAK) are not satisfied with the condition that Nagari are notapplied in the City Government. KAK claims as a holder of authority over the area of Bukittinggi cityis a source of strength to impose their demands. However during the reign of the new order, KAKlosing their existence and influence over local politics. Losing their influence on formal governance,make KAK indigenous leaders trying to restore the system of Nagari Government which will give aspace for them to power. There are indications that KAK demand is an attempt to restore the power oftraditional elites. KAK movement more motivated by political interests to gain access andrepresentation of their group within local government. The movement dynamics is closely linked withthe interests of the actors to find support in a particular political event. The indigenous elite(traditional leaders) as the initiators have not obtained a good representation as politically, culturallyand economically in local politics.